Penggunaan EFI scanner sebagai media pembelajaran untuk meningkatkan minat, motivasi, dan prestasi belajar siswa - I Gusti Made Adnyana; Wardan Suyanto (Jurnal Pendidikan Vokasi, 2013)
Penelitian ini bertujuan untuk meningkatkan minat, motivasi, dan prestasi belajar siswa pada mata diklat Memelihara/Servis dan Memperbaiki Engine Management System melalui penggunaan EFI Scanner sebagai media pembelajaran. Penelitian ini merupakan penelitian tindakan kelas model Piggot-Irvine. Subjek penelitian ini adalah siswa kelas XII TKR–1 SMKN 3 Singaraja, Bali yang berjumlah 30 orang. Data minat dan motivasi belajar diambil dengan menggunakan angket. Data prestasi belajar diambil dengan penilaian unjuk kerja melalui observasi terstruktur. Data minat dan motivasi belajar siswa dianalisis dengan deskriptif kuantitatif kemudian dibandingkan dengan standar acuan menjadi deskriptif kualitatif untuk menentukan minat dan motivasi belajar siswa dalam kategori tertentu. Data prestasi belajar siswa dianalisis dengan deskriptif kuantitatif untuk mengetahui ketercapaian nilai KKM. Rata-rata minat belajar siswa sebesar 81,08% dan motivasi belajar siswa sebesar 82,31% termasuk pada kategori tinggi. Dari hasil praktik, 43% siswa mencapai nilai KKM pada siklus I sementara pada siklus II, 90% siswa mencapai nilai KKM. USING EFI SCANNER AS A TEACHING MEDIUM FOR INCREASING STUDENTS' INTEREST, MOTIVATION, AND ACHIEVEMENTAbstractThis research aims to increase students' interest, motivation, and achievement in the training subject Maintenance and Service of Engine Management System through the use of EFI scanner as a teaching medium. This research is a Piggot-Irvine Model of classroom action research. The research subjects were 30 students of class XII TKR–1 SMKN 3 Singaraja, Bali. The instrument for data collection in this research was a questionnaire for data of learning interest and learning motivation.The data for the learning achievement were collected by performance assessment through structured observation. The data of learning interest and learning motivation were analyzed descriptively and quantitatively and converted/compared with a reference standard to determine into a descriptive qualitative to determine the students having learning interest and learning motivation in a particular category. The data for the learning achievement were analyzed descriptively and quantitatively to determine the accomplishment of the minimum accomplishment criteria.The students' average interest and motivation score is 81.08%, and 82.31% students are in the high category. From the results of the practice, 43% students reached the minimum accomplishment criteria in the first cycle while in the second cycle 90% students reached the minimum accomplishment criteria.